2017
DOI: 10.1093/mnras/stx880
|View full text |Cite
|
Sign up to set email alerts
|

X-ray observations of FO Aqr during the 2016 low state

Abstract: We present the first ever X-ray data taken of an intermediate polar, FO Aqr, when in a low accretion state and during the subsequent recovery. The Swift and Chandra X-ray data taken during the low accretion state in July 2016 both show a softer spectrum when compared to archival data taken when FO Aqr was in a high state. The X-ray spectrum in the low state showed a significant increase in the ratio of the soft X-ray flux to the hard X-ray flux due to a change in the partial covering fraction of the white dwar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 44 publications
5
48
0
Order By: Relevance
“…X-ray observations (Kennedy et al 2017) show that the mass-transfer rate decreased by about one order of magnitude. Due to solar conjunction, few data are available for the descent to the low state, which has been rapid (time scale of weeks) as compared to the recovery time.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray observations (Kennedy et al 2017) show that the mass-transfer rate decreased by about one order of magnitude. Due to solar conjunction, few data are available for the descent to the low state, which has been rapid (time scale of weeks) as compared to the recovery time.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of star spots has been inferred for the first time in the donor of the IP AE Aqr (Hill et al 2016), although it has never been observed to undergo state changes. Star spots have been claimed to be responsible for the low states of Polars and of the state changes in FO Aqr (Kennedy et al 2017). We note that, interestingly, star spots at L1 should produce random (e.g.…”
Section: Discussionmentioning
confidence: 69%
“…This X-ray emission is then pulsed at the spin period of the WD (disc-accretion), at the beat (disc-less) or at both periods in the case of disc overflow (Hellier 1995). The vast majority of IPs are persistent systems, but a small subgroup including FO Aqr, AO Psc, and V1223 Sgr, showed low accretion states (Garnavich & Szkody 1988;Kennedy et al 2017;Littlefield et al 2018). Such fading is believed to be due to a temporarily reduction of the mass transfer rate from the donor star (Livio & Pringle 1994).…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that the phase shift could be the result of a change in the accretion geometry but cautioned that it needed to be confirmed. Fortunately, Kennedy et al (2017) dug deeper into the issue and found that the purported phase shift was attributable to a minuscule inaccuracy in the WD spin period from Kennedy et al (2016), propagated across 2 yr. Although the period was constant throughout the K2 observations, there were small phase shifts of the spin pulse in response to the system's overall luminosity, and these shifts caused the Lomb-Scargle periodogram to yield a period that was inaccurate by just a few milliseconds (Kennedy et al 2017).…”
Section: Spin Periodmentioning
confidence: 99%
“…Fortunately, Kennedy et al (2017) dug deeper into the issue and found that the purported phase shift was attributable to a minuscule inaccuracy in the WD spin period from Kennedy et al (2016), propagated across 2 yr. Although the period was constant throughout the K2 observations, there were small phase shifts of the spin pulse in response to the system's overall luminosity, and these shifts caused the Lomb-Scargle periodogram to yield a period that was inaccurate by just a few milliseconds (Kennedy et al 2017). There are two critical takeaways from Kennedy et al (2017) about the spin ephemeris: (1) the phase shift from Paper I was not of astrophysical origin and, (2) more broadly, modeling a light curve of FO Aqr with a periodic function is not a reliable means of extracting either the time-averaged spin period or the time of one fiducial photometric maximum.…”
Section: Spin Periodmentioning
confidence: 99%